A Small Festival for Small People: The WeeFestival as Advocacy - Fitzsimmons Frey, Heather (Theatre Research in Canada / Recherches théâtrales au Canada, 2019)
The WeeFestival, English Canada’s first performance festival dedicated to children from ages 0 to 5, acts as an advocate for the early years demographic and for the artists who create for them through three key elements of festival structure: programming, space, and creative/artistic exchange. Engaging with research by Ben Fletcher-Watson, Lise Hovik, Matthew Reason, and Adele Senior, this article uses company archives, artist interviews, and the writer’s personal experiences to analyze how the WeeFestival temporarily establishes an alternative public sphere that challenges policy-makers, funders, and artists to rethink relationships between arts, very young citizens, and urban life. Even though very young citizens may not initially know that they want to experience art, the festival attends to the interests and responses of young people, demonstrates respect for their capacity to be emotionally and intellectually engaged by artful and thoughtful productions, and establishes festivalized spaces that put an alternative public sphere into action, gesturing to the possibility of real social change. Taking into account the significance of programming for artists, educators, and policy-makers alongside the significance of meaningful audience-artist exchange, the analysis suggests that events like the WeeFestival have the capacity to gently shift how urban dwellers perceive very young children and the way they interact with the arts in daily life.